2022
DOI: 10.1175/jcli-d-21-0235.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Stratospheric Polar Vortex Shift on the East Asian Trough

Abstract: Impacts of stratospheric polar vortex shift on the wintertime East Asian trough (EAT) on intraseasonal time scales are investigated using a reanalysis dataset and a climate model. The result based on composite analysis shows that the shift of the stratospheric polar vortex toward eastern Siberia (ES-shift event) is associated with higher geopotential height at 500 hPa than normal over East Asia, corresponding to the weakened EAT. Furthermore, the simulated EAT is also weakened when nudging the stratospheric st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The enhanced westward forcing exerted by IGWs in the westerly phase disruption is also confirmed by MERRA-2 data (Kang et al, 2020), and our results further investigate the observed GW during 2015/16D in detail. This study presents the activity characteristics of IGWs in the western Pacific during 15/16D from the perspective of observation for the first time, which can be used to supplement and confirm the discussion on the role of multi-scale wave activity to the mean flow by various models and reanalysis data (Chang et al, 2022;Coy et al, 2017;Garcia & Richter, 2019;Holt et al, 2016;Kawatani et al, 2009;Kim & Achatz, 2021;Li et al, 2020;Newman et al, 2016;Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 88%
“…The enhanced westward forcing exerted by IGWs in the westerly phase disruption is also confirmed by MERRA-2 data (Kang et al, 2020), and our results further investigate the observed GW during 2015/16D in detail. This study presents the activity characteristics of IGWs in the western Pacific during 15/16D from the perspective of observation for the first time, which can be used to supplement and confirm the discussion on the role of multi-scale wave activity to the mean flow by various models and reanalysis data (Chang et al, 2022;Coy et al, 2017;Garcia & Richter, 2019;Holt et al, 2016;Kawatani et al, 2009;Kim & Achatz, 2021;Li et al, 2020;Newman et al, 2016;Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 88%
“…Currently, the dynamic processes in near space have become a research hotspot in the context of climate change, as they can provide an important basis for ensuring the normal operation of spacecraft and improving the accuracy of numerical weather prediction [18,19]. Gravity waves, Kelvin-Helmholtz instability (KHI), and turbulence, as important physical processes in near space, have been extensively studied through various types of detection equipment and numerical simulations [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%